2007
DOI: 10.1111/j.1399-3038.2006.00501.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related difference in immune responses to respiratory syncytial virus infection in young children

Abstract: There have been longitudinal studies of the developmental change of the immune system during the first year of life. The aim of this study was to investigate if there is any age-related difference in cytokine responses to respiratory syncytial virus (RSV) infection between the patients under 6 months of age and the patients over 12 months of age compared with age-matched controls. Forty-five children < or =24 months of age who were admitted with acute RSV bronchiolitis were enrolled. The patients were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
5
15
0
2
Order By: Relevance
“…Several studies have shown that there are differences in cytokine profiles, T cell proliferation and Natural Killer Cell (NKC) activity between young children and adults. [30][31][32][33] This is supported by the fact that both re-infection and prolonged infection of HRV subtypes were only seen in the youngest children of the study population. Further studies are needed to unravel the association between age and the diversity of HRVs.…”
Section: Discussionsupporting
confidence: 60%
“…Several studies have shown that there are differences in cytokine profiles, T cell proliferation and Natural Killer Cell (NKC) activity between young children and adults. [30][31][32][33] This is supported by the fact that both re-infection and prolonged infection of HRV subtypes were only seen in the youngest children of the study population. Further studies are needed to unravel the association between age and the diversity of HRVs.…”
Section: Discussionsupporting
confidence: 60%
“…The differences in findings could be related to cellular location of cytokine production and age of the study population. In another study, Chung et al found that younger children with RSV infection (<6 months old) had diminished IFN-γ levels 19. In our study, we found that children infected at younger than 6 months of age were at increased risk of developing asthma at 6 years of age, however, they did not have significantly lower levels of INF-γ compared to the older children (Table 2).…”
Section: Discussionsupporting
confidence: 40%
“…Longitudinal studies on the development of the immune system have shown a significant age-related development during postnatal early life difference during early life4-6). Our previous study showed significant developmental changes in cytokine responses during the early years of life7). We also observed significant age-related differences in interferon (IFN)-γ and interleukin (IL)-13 responses in children with acute respiratory syncytial virus (RSV) bronchiolitis7).…”
Section: Introductionmentioning
confidence: 84%